Studi Kesesuaian Pemanfaatan Lahan terhadap Peraturan Pengelolaan Daerah Aliran Sungai (DAS) di Kabupaten Gorontalo: Tinjauan Ekologis, Normatif, dan Aksiologis - Roland Kasim; Mahludin S. Baruwadi; Hasim Hasim (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the compatibility between land use practices and watershed management regulations in Gorontalo Regency through ecological, normative, and axiological approaches. Rapid land cover changes from the upstream to downstream areas, particularly in the Biyonga, Alo-Pohu, and Limboto watersheds, have caused severe impacts such as increased erosion, sedimentation, and reduced hydrological function. The study employs a qualitative analysis using a literature-based method, reviewing key scientific articles from Jurnal Ilmu Lingkungan Universitas Gadjah Mada, Sustainability (MDPI), and Engineering, Technology & Applied Science Research, as well as regulatory documents such as Government Regulation No. 37 of 2012, Government Regulation No. 27 of 2023, Regional Regulation of Gorontalo Province No. 11 of 2014, and Governor Regulation No. 19 of 2019. The findings reveal that, ecologically, the conversion of agricultural lands into settlements has increased sediment yield and reduced soil infiltration capacity. Normatively, most land use activities remain inconsistent with soil and water conservation regulations. Axiologically, there is a gap between sustainability values embedded in policy and the community’s practical behavior in managing land resources. This study highlights the need for integrating scientific, legal, and ethical perspectives to strengthen sustainable watershed management in Gorontalo. Therefore, the findings are expected to serve as a policy recommendation framework for local governments in developing adaptive and ecologically grounded watershed management strategies.